Brazil : Financial Sector Assessment Program-Technical Note on Bank Resolution, Financial Sector Safety Nets, Crisis Prevention and Management. (IMF Staff Country Reports; Country Report ;, 2018)
Important improvements have been made to the bank resolution, safety net and crisis management framework since the last FSAP. The resolution framework has been strengthened with the creation, within the Banco Central do Brasil (BCB), of a new Resolution Department, and requirements for recovery and resolution planning have been established. The early intervention powers of the BCB are robust and flexible. Notwithstanding this progress, the current framework has limitations that are broadly acknowledged by the authorities. Resolution powers are incomplete and no formal inter-agency arrangements for crisis management are in place. The BCB has taken the lead in preparing a comprehensive draft law (the 'Draft Law') that seeks to introduce a new resolution regime in line with international best practices. This FSAP takes place therefore at a critical juncture. It provides recommendations on the design features of the new resolution regime, examining the existing framework as well as the areas not addressed in the Draft Law.